The Effectiveness of Blended Learning on Training Participant’s Learning Outcomes in The Financial Transaction Reporting Training Program - Bilqis, Rizqa Aisyah (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2025)
One of the initiatives made in preventing and eradicating money laundering and terrorism financing is to enhance the competency of PPATK stakeholders through training. PPATK Education and Training Center has organized blended learning training, which combines synchronous and asynchronous learning. The purpose of this research was to measure the effectiveness of financial transaction reporting training held using the blended learning method on the learning outcomes of the reporting party (Foreign Exchange Traders) who are one of the PPATK stakeholders. Kirkpatrick's Four Level Evaluation model is used as an evaluation model in measuring the effectiveness of training with the blended learning method at the PPATK Education and Training Center. This evaluation model is a reference in implementing the evaluation of the implementation of a training program. In this research, there are evaluation limitations only up to level 1 and level 2. Evaluation at level 1 or reaction is used to assess participant satisfaction and their perceptions of the quality of training, while evaluation at level 2 or learning is used to assess the level of participant understanding of the knowledge or training materials that have been provided. The analytical method employed involves descriptive statistical analysis using Microsoft Excel for the questions that were answered by the participants using a Likert scale, followed by a paired statistical t-test and measurement of the effect size using Cohen's d analysis to assess the impact of the blended learning method on the results. The research results showed that the level of participant satisfaction was very good. The results of learning evaluations through pre-test and post-test show significant differences in results. Furthermore, the effect size statistical analysis produced a Cohen's d value, showing that the blended learning method has a large influence on participant learning outcomes. Thus, Financial Transaction Reporting training for Reporting Parties using blended learning has runs effectively.